Metabolic syndrome in first episode Schizophrenia, based on the National Mental Health Registry of Schizophrenia (NMHR) in Hospital Kuala Lumpur, 10 year naturalistic follow up study / Lee Muh Haur Albert - Lee, Muh Haur Albert (2016)
Metabolic Syndrome is a worrying issue globally. Patients with Schizophrenia have a higher risk then normal in developing this disease. This is the first 10 year retrospective outcome study of metabolic syndrome and schizophrenia in Malaysia. Objective: To investigate the rate of metabolic syndrome in schizophrenia over ten years and its associated factors. Method: 174 patients who were registered with the National Mental Health Registry of Schizophrenia (NMHR) Hospital Kuala Lumpur in 2004 - 2005, were analyzed and their progress was reviewed over the last ten years. Results: After 10 years, all patients weight, body mass index, fasting blood sugar and blood pressure are significantly increased. A total of 63 subjects (36.2%) developed metabolic syndrome while 36 (23.2%) are hypertensive, and 41 (28.1%) are diabetic. There are 3 variables which are significantly associated with metabolic syndrome namely Intra-Muscular Fluphenthixol depot (CI=1.05-5.09, OR:0.84, p=0.039), physical activity (CI=0.13-1.00, OR: -1.04, p=0.050), and substance use disorder (CI=1.40, 13.89, OR: 1.48, p=0.012). Comorbid substance abuse is still significantly associated 10 with metabolic syndrome despite adjusting for physical activity and intra-muscular depot. Female gender is more likely to have an increase in systolic blood pressure (CI=1.08- 11.82, OR: 6.45, p=0.019), while the low physical activity group has lower change in systolic BP (CI=0.33-15.60, OR: 7.96, P=0.041). High physical activity was also associated with an increase in diastolic BP (DBP) (CI= 1.51-12.91, OR: 7.21, P=0.014). Atypical antipsychotic group is 1.91 times more likely to have an increase in BMI compared to those on typical antipsychotics. Conclusion: Schizophrenia patients have a higher risk of developing metabolic syndrome. Factors which are significant in causing a greater rise in Metabolic Syndrome are the usage of IM depo fluanxol (flupentixol), comorbid substance abuse, and the lack of physical activity. A more holistic approach in assisting patients to modify the modifiable risk is needed in the management of schizophrenia. More research needs to be done in the long-term outcome of patients with schizophrenia to aid in the long term planning and management of this chronic disease.